Comparative analysis of lithium-iron-phosphate and sodium-ion energy storage devices - Al_Issa, Huthaifa A.; Qawaqzeh, Mohamed; Hussienat, Lina Hani; Oksenych, Ruslan; Miroshnyk, Oleksandr; Moroz, Oleksandr; Trunova, Iryna; Paziy, Volodymyr; Halko, Serhii; Shchur, Taras (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2025)
Energy storage is the process of accumulating, releasing, and managing energy using storage devices. Today, this principle of energy storage is playing an important role in energy supply. As renewable sources become more and more responsible for energy production. Moreover, since it is not possible to regulate the amount of energy from renewable sources, it is necessary to store energy during periods of lower demand or higher production, from sources such as solar and wind energy. Over the past century, a wide range of energy storage technologies have been developed, from large-scale hydroelectric power plants to advanced electrochemical storage. Hydroelectric power plants remain the main method of long-term energy storage due to their high capacity and durability. At the same time, lithium-iron-phosphate and sodium-ion batteries open up new opportunities for energy storage at the local level, making them promising for integration into modern power systems. In addition, the efficient use of energy storage can minimize the risks of electricity shortages during critical periods and ensure the stability of the power system. This is achieved due to the ability of energy storage to effectively level the load, compensate for fluctuations in renewable energy generation, and provide reliable backup power. In particular, LiFePO4 and Na-Ion technologies demonstrate high energy efficiency, which allows them to be integrated into various segments of the power system - from household devices to large-scale industrial plants. Their use also helps to reduce the carbon footprint of the energy sector, which is important for achieving sustainable development goals. In this paper, we compare two types of electrochemical storage devices - LiFePO4 and Na-Ion. Particular attention will be paid to their durability, energy efficiency, materials from which they are made, and technical characteristics. Also, their economic feasibility and prospects for implementation in commercial and domestic applications will be assessed.